Concessão de permissão a dados de saúde baseada em contratos inteligentes em plataforma de blockchain - Junqueira, Natália Rodrigues (2020)
The appearance of wearable devices has allowed people to monitor their own health status even though they are in a home environment. In addition, there has also been an awareness of the population that health is something fundamental, causing the interest of people to control their own health, to track and analyze this personal health data. The person-centered approach to medicine emerged with the aim of enabling control of these health data for the people to whom they really belong, that is, the patient himself. In this way, a patient could not only monitor this data, but effectively decide who can and cannot access it. Blockchain is a technology that emerged with the aim of making secure transactions over the internet without the need for a trusted third party; in the context of health data, the trusted third party would be a hospital or an entity that stores and controls the data collected from patients. This research aims to develop a blockchain-based architectural solution for granting permission to access patient health data collected by a remote patient monitoring system through relationships on a social network. In order to validate the solution, smart contracts were implemented to identify, track data and allow the granting of permission to access patient data. Smart contracts were developed and tested using the blockchain platform Hyperledger Fabric.